Numerical investigations of convective heat transfer for lattice settings in brick tunnel Kiln: CFD simulation with experimental validation. (1st August 2021) - Refaey, H.A.; Alharthi, Mathkar A.; Salem, M.R.; Abdel-Aziz, Ali A.; Abdelrahman, H.E.; Karali, M.A.
Highlights: Numerical simulation for the cooling process in brick tunnel kiln are presented. Four lattice bricks settings are simulated. New lattice setting is presented using CFD simulation. As brick spacing increased an augmentation of 15.3% is founded in longitudinal brick. Abstract: The flow characteristics and heat transfer around brick model settings are very important fields of investigation to get over the problem of energy consumption and production process. The present paper introduces a numerical investigation of convective heat transfer for lattice settings in brick tunnel kiln. A numerical CFD analysis using the ANSYS-FLUENT package is used to simulate convective heat and fluid flow inside the cooling zone of the tunnel kiln. Three different settings are simulated and validated with published data. In addition, a fourth new setting is designed and simulated numerically. The results reveal that using CFD k-ω BSL turbulent model gives a good agreement with the published experimental data compared to the other turbulence models. Therefore, a new design of bricks used in buildings could be produced by examining it firstly using CFD. It can be used in study new settings and give acceptable results. Moreover, the longitudinal and transversal average Nusselt number are improved by increasing the space between bricks and columns. As the brick spacing increased from 5 to 16 mm a maximum augmentation of about 15.3% is founded in longitudinal brick at wall column in setting 11 at Re = 14, 674. While, as column spacing increased from 19 to 58 mm a maximum augmentation of about 15.66% is gained for a longitudinal brick at the middle column in setting 11 at Re = 14, 674.